ITEM CHARACTERISTICS ANALYSIS USING THE RASCH MODEL IN THE DEVELOPMENT OF READING LITERACY INSTRUMENTS FOR ELEMENTARY SCHOOLS STUDENTS - Wiradika, I Nyoman Indhi; Retnawati, Heri (PROGRES PENDIDIKAN, 2022)
Literacy is a basic reading skill in modern society. The development of reading literacy questions is needed to be useful as an assessment function. The development of reading literacy questions needs to pay attention to the principle of conformity with indicators and pay attention to the characteristics of the items. A total of 167 fifth grade elementary school students were sampled in the test instrument for the reading literacy test. Instrument testing was carried out in two stages; first, content validity testing by seven experts, secondly analysis of model fit and item difficulty to determine item characteristics. The results showed that based on the results of expert judgment, 17 items were valid and 1 item had moderate validity. Items with moderate validity are S18 items that are classified as evaluating and reflecting type questions at level 6. Further analysis using the Rasch model obtained 2 items in the very easy category, 14 items in the easy category, 1 item in the difficult category and 1 item in the difficult category. very difficult category. With a distribution of difficulty levels, 11% of very easy questions, 78% of easy questions, 6% of difficult questions, and 6% of very difficult questions.